2007
DOI: 10.1002/jbm.a.31345
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of medical‐grade polyurethane by cyanurchloride‐activated tetraether lipid (a new approach for bacterial antiadhesion)

Abstract: The surface of high-grade medical polyurethane was chemically modified and coated with tetraether lipid, employing cyanurchloride as coupling agent. The surfaces were initially grafted with hexamethylene diisocyanate and subsequently treated with water or hexamethylene diamine to generate free amino groups on the surface. This provides a convenient way for covalent coupling of tetraether lipids. These lipid-coated surfaces were investigated for bacterial adhesion using Pseudomonas aeruginosa. All lipid-coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The functionalization of the TELs was performed as recently described by Saatesh et al 15 Briefly, the purified lipids were dissolved in dry chloroform/methanol 1:1 and NaHCO 3 (1.5 g per 100 mg lipid) was added. The mixture was stirred under reflux for 1 hour.…”
Section: Functionalization Of the Lipids With Cyclmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization of the TELs was performed as recently described by Saatesh et al 15 Briefly, the purified lipids were dissolved in dry chloroform/methanol 1:1 and NaHCO 3 (1.5 g per 100 mg lipid) was added. The mixture was stirred under reflux for 1 hour.…”
Section: Functionalization Of the Lipids With Cyclmentioning
confidence: 99%
“…The CyCl moiety is amine reactive and coatings composed of CyCl functionalized GDGT lipids (GDGT*) were successfully prepared and characterized, recently. 3,[14][15][16] However, the as yet described method for preparing GDGT* coatings requires several incubation steps with organic solvents and thus potential conflicts for biomedical applications. The aim of this study was to prepare stable, covalently tethered TEL membranes on solid supports via the vesicle spreading technique in an aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…bipolar membrane spanning lipids from thermoacidophilic archaea, were presented as an interesting new class of linker molecules. [34][35][36][37][38][39] By a simple selfassembling process, a stable, highly ordered impermeable TEL monolayer ($4 nm) with biomembrane-like properties is formed. The covalent immobilization of this thin lipid layer on surfaces can be achieved easily when the lipid headgroups are functionalized with cyanuric chloride.…”
Section: Introductionmentioning
confidence: 99%
“…The covalent immobilization of this thin lipid layer on surfaces can be achieved easily when the lipid headgroups are functionalized with cyanuric chloride. [35][36][37]39 An outstanding property of TELs is their excellent stability against oxidation, acidic and basic hydrolysis as well as biodegradation, which is based on the fully saturated character of the methyl branched alkyl chains. 34 Moreover, biocompatibility analyses revealed that TELs are both nontoxic and immunologically inert and, additionally, exhibit antifouling activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation